Recent progress in orodispersible films‐mediated therapeutic applications: A review - Yu Tian; Jiangtao Lin; Hongshu Jing; Quan Wang; Zhihua Wu; Yourong Duan (MedComm – Biomaterials and Applications, 2023)
Abstract Orodispersible films (ODFs) as a relatively novel delivery platform have increasingly attracted enormous attention owing to their various advantages compared to conventional oral dosage forms, including fast disintegration, ease of administration without consumption of water, and rapid absorption of incorporated drug, high patient compliance for pediatrics, geriatrics and patients with swallowing difficulties. This review aims to summarize the developments and possibilities that ODFs as the potential carrier for chemical drugs, vaccine, probiotics, and herbal extracts. Especially, with the outbreak of coronavirus disease 2019 (COVID‐19), the advantages of ODFs related to ease of transporation and distribution without cold‐chain as well as low‐cost manufacturing make ODFs a promising carrier for vaccines against COVID‐19. Subsequently, the current therapeutic applications of ODFs delivered either locally or systemically for potential patients suffering from various diseases are discussed, including oral inflammation, cardiovascular diseases, pain disorders, nausea and vomiting, mood or mental disorders, erectile dysfunction and pulmonary diseases. Finally, this review provides overview of the novel inkjet printing and three‐dimensional printing techniques, and the possibility of extemporaneous preparation for ODFs in hospital pharmacies via printing techniques are discussed as well.